Understanding Religious Tolerance Through the Human Rights Lens: The Implication for Religious Education - Marhumah; Zulkipli Lessy; Sri Sumarni; Miftahur Rohman (Jurnal Pendidikan Agama Islam, 2025)
Purpose – The study was conducted to comprehend the way Graduate School students of UIN Sunan Kalijaga Yogyakarta, Indonesia, define tolerance, and view its significance and evidence-based practices that benefit the community and society. The comprehension could be used to mitigate conflicts and tensions which in turn positively affect societal living conditions. All of these aim to eradicate intolerance toward minority groups and ultimately strengthen the national harmony. Methods – The qualitative study was run through interview with the students. Additionally, a literature review was also implemented to enrich primary data. Twelve students of School of Graduate Studies of UIN Sunan Kalijaga Yogyakarta were solicited through a convenience sampling, in which invitation letters were sent to them together with the informed consent. Those who responded to the letters were recruited to be participants. Data was gathered through individual interviews, and a focus group discussion was conducted at the end to consolidate overall data. We analyzed the data through intensive reading of verbatim transcripts prior to categorization establishment. Then, clusters were created for establishing themes. Findings – Understandings of religious tolerance can be explored in some critical issues such as freedom to religion in light of human rights and limitation, concepts of tolerance, significance of religious tolerance, evidence-based practice of such tolerance, and understanding benefits for societal harmony. Research implications/limitations – The twelve participants involving in the study imply significant impacts to Indonesian society as the Indonesian government is intensively maintaining tolerance and harmony for the nation unity despite the different background society’s existence. The small number of the participants cannot lessen the research validity because the study does not seek generalizability but understands the knowledge and experience of the participants. Originality/value – The research contributes to boost both individual and society for promoting religious tolerance values.